Reduced P53 staining in actinic keratosis is associated with squamous cell carcinoma: A preliminary study - D R Neto Pimentel; MMA Alchorne; N S Michalany; MAMM Abreu; R C Borra (Wolters Kluwer Medknow Publications, 2013)
Background : Actinic keratosis (AK) is a cutaneous neoplasm caused by prolonged sun exposure, and may progress into squamous cell carcinoma (SCC). The p53 gene plays a central role in the development of SCC, and mutations in this gene are found in 90% of SCC and up to 100% of AK cases. Objective: To identify AK cases that are highly susceptible to developing SCC. Materials and Methods: Fifty-six AK cases were classified into two groups: AK adjacent to "normal" skin and AK adjacent to SCC. The groups were compared based on epithelial atypia, inflammation, solar elastosis, histopathological AK classification and p53 protein expression. Results: Of the 56 AK cases analyzed, 23% were associated with SCC. The types of AK observed were classified as follows: common, hypertrophic , atrophic , acantholytic , pigmented and bowenoid . SCC was associated with common and hypertrophic AK, and p53 staining was observed in 78% of AK cases. The mean difference in p53 immunopositivity between common AK cases associated with SCC (17%) and not associated with SCC (45.4%) was significant (p=0.011). Conclusions: Hypertrophic and common AK are associated with SCC, and the low percentage of p53 immunopositivity in the common type indicates a greater probability of developing into SCC.